'We walked side by side through the whole thing': A mixed‐methods study of key elements of community‐based participatory research partnerships between rural Aboriginal communities and researchers. (4th August 2020) - Snijder, Mieke; Wagemakers, Annemarie; Calabria, Bianca; Byrne, Bonita; O'Neill, Jamie; Bamblett, Ronald; Munro, Alice; Shakeshaft, Anthony
Abstract: Objectives: To advance the rural practice in working with Aboriginal communities by (a) identifying the extent of community partners' participation in and (b) operationalising the key elements of three community‐based participatory research partnerships between university‐based researchers and Australian rural Aboriginal communities. Design: A mixed‐methods study. Quantitative survey and qualitative one‐on‐one interviews with local project implementation committee members and group interviews with other community partners and project documentation. Setting: Three rural Aboriginal communities in New South Wales. Participants: Thirty‐seven community partners in three community‐based participatory research partnerships of which 22 were members of local project implementation committees and 15 were other community partners who implemented activities. Intervention: Community‐based participatory research partnerships to develop, implement and evaluate community‐based responses to alcohol‐related harms. Main outcomes measures: Community partners' extent of and experiences with participation in the community‐based participatory research partnership and their involvement in the development and implementation processes. Results: Community partners' participation varied between communities and between project phases within communities. Contributing to the community‐based participatory research partnerships were four key elements of the participatory process: unique expertise of researchers and community‐based partners, openness to learn from each other, trust and community leadership. Conclusion: To advance the research practice in rural Aboriginal communities, equitable partnerships between Aboriginal community and research partners are encouraged to embrace the unique expertise of the partners, encourage co‐learning and implement community leadership to build trust.